Flexible asset purchases and repo market functioning - Adriana Grasso; Andrea Poinelli (European Central Bank (ECB), 2025)
Flexibility has progressively become a distinctive feature of the implementation of the Eurosystem's asset purchases. In its many manifestations, flexibility has also been used by asset managers in the daily selection of sovereign bonds to limit the impact of asset purchases on repo market specialness. This study shows that, since the inception of the Public Sector Purchase Programme, flexible purchases of bonds greatly mitigated the Eurosystem's footprint on the repo market.
Keywords: E50; E52; E58; G10; G18; 330; Asset Purchases; Flexibility; Market Neutrality; Specialness; Repo